Synergistic simultaneous NOx and CO abatement over transition metal-modified VWTi catalysts with robust SO2/H2O tolerance - Jiahao Cheng; Yuewei Li; Xingxing Cheng; Xiaocui Fan; Aihua Xu; Zhiqiang Wang; Fuqiang Guo; Makhsumov Ilkhom Burkhonovich (Chemical Engineering Journal, 2026)

An analysis of urban land subsidence susceptibility based on complex network - Yiyue Wang; Runyu Fan; Jining Yan; Min Jin; Xinya Lei; Yuewei Wang; Weijing Song (Natural Hazards, 2025)

Optimized air-ground data fusion method for mine slope modeling - Dan Liu; Man Huang; Zhigang Tao; Chenjie Hong; Yuewei Wu; En Fan; Fei Yang (Journal of Mountain Science, 2024)

Mitochondria-targetable small molecule fluorescent probes for the detection of cancer-associated biomarkers: A review - Xue Yu; Yunong Huang; Yunqi Tao; Li Fan; Yuewei Zhang (Analytica Chimica Acta, 2024)

Long‐term nitrogen and phosphorus addition have stronger negative effects on microbial residual carbon in subsoils than topsoils in subtropical forests - Linjie Fan; Yuewei Xue; Donghai Wu; Meichen Xu; Andi Li; Baixin Zhang; Jiangming Mo; Mianhai Zheng (Global Change Biology, 2024)
Highly weathered lowland (sub)tropical forests are widely recognized as nitrogen (N)‐rich and phosphorus (P)‐poor, and the input of N and P affects soil carbon (C) cycling and storage in these ecosystems. Microbial residual C (MRC) plays a crucial role in regulating soil organic C (SOC) stability in forest soils. However, the effects of long‐term N and P addition on soil MRC across different soil layers remain unclear. This study conducted a 12‐year N and P addition experiment in two typical subtropical plantation forests dominated by Acacia auriculiformis and Eucalyptus urophylla trees, respectively. We measured plant C input (fine root biomass, fine root C, and litter C), microbial community structure, enzyme activity (C/N/P‐cycling enzymes), mineral properties, and MRC. Our results showed that continuous P addition reduced MRC in the subsoil (20–40 cm) of both plantations ( A. auriculiformis : 28.44% and E. urophylla : 28.29%), whereas no significant changes occurred in the topsoil (0–20 cm). N addition decreased MRC in the subsoil of E. urophylla (25.44%), but had no significant effects on A. auriculiformis . Combined N and P addition reduced MRC (34.63%) in the subsoil of A. auriculiformis but not in that of E. urophylla . The factors regulating MRC varied across soil layers. In the topsoil (0–10 cm), plant C input (the relative contributions to the total variance was 20%, hereafter) and mineral protection (47.2%) were dominant factors. In the soil layer of 10–20 cm, both microbial characteristics (41.3%) and mineral protection (32.3%) had substantial effects, whereas the deeper layer (20–40 cm) was predominantly regulated by microbial characteristics (37.9%) and mineral protection (18.8%). Understanding differential drivers of MRC across soil depth, particularly in deeper soil layers, is crucial for accurately predicting the stability and storage of SOC and its responses to chronic N enrichment and/or increased P limitation in (sub)tropical forests.

Long-term exposure to ambient fine particulate matter-bound polycyclic aromatic hydrocarbons and cancer mortality: A difference-in-differences approach - Yingxin Li; Zhaoyu Fan; Wenfeng Lu; Ruijun Xu; Tingting Liu; Likun Liu; Gongbo Chen; Ziquan Lv; Suli Huang; Yun Zhou; Yuewei Liu; Hong Sun (Chemosphere, 2023)

A halogen-free hyper-crosslinked ionic polymer for efficient multi-conversion of CO2 into carbonates under mild conditions, with a combination of theoretical study - Bowen Jiang; Jia Liu; Wenjie Xiong; Meiling Weng; Jigang An; Yuewei Fan; Leizhi Zheng; Guoqiang Yang; Zhibing Zhang (Chemical Engineering Journal, 2023)

A lipid droplet-targeting fluorescent probe for specific H2S imaging in biosamples and development of smartphone platform - Xue Yu; Yunong Huang; Ning Zhang; Qi Zan; Xiaodong Wang; Zhuping Jin; Li Fan; Chuan Dong; Yuewei Zhang (Analytica Chimica Acta, 2023)

A survey of machine learning and deep learning in remote sensing of geological environment: Challenges, advances, and opportunities - Wei Han; Xiaohan Zhang; Yi Wang; Lizhe Wang; Xiaohui Huang; Jun Li; Sheng Wang; Weitao Chen; Xianju Li; Ruyi Feng; Runyu Fan; Xinyu Zhang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

A deep learning method for predicting lower troposphere temperature using surface reanalysis - Hang Fan; Yubao Liu; Yang Li; Yuewei Liu; Jing Duan; Lei Li; Zhaoyang Huo (Atmospheric Research, 2023)

Human papillomavirus prevalence among men who have sex with men in China: a systematic review and meta-analysis - Yiguo Zhou; Yi-Fan Lin; Lei Gao; Jianghong Dai; Ganfeng Luo; Lanying Li; Tanwei Yuan; Peiyang Li; Yuewei Zhan; Yanxiao Gao; Huachun Zou (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

How Deep Might Myoblasts Sense: The Effect of Substrate Stiffness and Thickness on the Behavior of Myoblasts - Shan Li; Feng Zhao; Yuewei Zhan; Xiaoyi Liu; Tingting Hun; Haokang Zhang; Changjun Qiu; Jingwen He; Zongchun Yi; Yan Sun; Yubo Fan (Journal of Medical and Biological Engineering, 2018)